Participation in Shadow Education in Church- and State-Maintained Schools: The Role of Cultural and Social Capital - Hegedűs, Gabriella; Csépes, Ildikó (Central European Journal of Educational Research, 2025)
Research on shadow education is often justified based on Bourdieu’s theory of capital as it is assumed to contribute to social inequalities. This paper focuses on the role of cultural and social capital and on the differences between state- and church-maintained schools in the North-Eastern parts of Hungary. Using a convenience sample and our own constructed measurement tool, a quantitative survey of secondary school language learners (N=711) was conducted to explore the relationship between the effectiveness of supplementary private language tutoring as well as the cultural and social capital of language learners in cross-sectoral comparisons. Our results highlight the positive correlation between the highest educational attainment of the mother, the participation rate in shadow education and language learners’ achievement. In our study, language learners whose mothers had a higher education level demonstrated greater efficiency, in terms of academic achievements. Despite being less successful in passing language examinations as a result of a lower social composition in denominational grammar schools, language learners could count on a higher level of support both from their language teachers - who were better able to support their students to progress at their own pace - and from their classmates and families, demonstrating that social capital had a compensating effect on their learning trajectories.